A case report on a rare disorder: Moyamoya (Indian Journal of Case Reports, 2021)
Moyamoya is a rare disease characterized by progressive endpoint stenosis of the internal carotid arteries of the internal intracranial portions due to smooth muscle hypertrophy in the vessel walls. Here, we present the case of a 17-year-old boy who has been admitted to a tertiary care hospital in India with complaints of major headache, multiple vomiting episodes, and difficulty in seeing the right half of things from the past 20 days. The computed tomography (CT) brain, magnetic resonance imaging, and cerebral angiogram were examined for the patient. He has been diagnosed with moyamoya disease based on the evaluation. The patient was, therefore, recommended for cerebral revascularization and performed successfully then discharged with stable condition.